2020
DOI: 10.3390/ijms21145093
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Peroxisome Proliferator-Activated Receptor (PPAR) Alpha and Gamma Agonists Prevents Corneal Inflammation and Neovascularization in a Rat Alkali Burn Model

Abstract: Peroxisome proliferator-activated receptor alpha (PPARα) and gamma (PPARγ) agonists have anti-inflammatory and anti-neovascularization effects, but few reports have tested the combination of PPARα and PPARγ agonists. In this study, we investigated the therapeutic effects of ophthalmic solutions of agonists of PPARα, PPARγ, and the combination in a rat corneal alkali burn model. After alkali injury, an ophthalmic solution of 0.05% fenofibrate (PPARα group), 0.1% pioglitazone (PPARγ group), 0.05% fenofibrate + 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…This implies PPARα activation could have potential for use as a preventive agent in patients with high risk of dry eye. Other cornea studies indicated therapeutic roles of PPARα agonists against corneal inflammation and neovascularization [ 110 , 111 ]. Corneal neovascularization is closely related to a reduction in corneal transparency which is important for visual acuity [ 112 , 113 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
See 1 more Smart Citation
“…This implies PPARα activation could have potential for use as a preventive agent in patients with high risk of dry eye. Other cornea studies indicated therapeutic roles of PPARα agonists against corneal inflammation and neovascularization [ 110 , 111 ]. Corneal neovascularization is closely related to a reduction in corneal transparency which is important for visual acuity [ 112 , 113 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“…Corneal neovascularization is closely related to a reduction in corneal transparency which is important for visual acuity [ 112 , 113 ]. In rat corneal alkali burn models, corneal neovascularization was seen and a topical injection of fenofibrate suppressed its neovascularization through upregulation of PPARα mRNA expression and suppression of IL-6, IL-1β, Vegf and Ang-2 mRNA expressions [ 110 , 111 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“…In ophthalmology, PPARs have recently been reported to affect inflammation, fibrosis, and angiogenesis [13,14,18,19]. However, there are few reports of the effects of PPARs on corneal epithelial wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of all subtypes of PPARs has been reported to suppress inflammation via inhibition of NF-κB [9,10]. In the field of ophthalmology, we previously reported the anti-inflammatory and anti-neovascular effects of PPARα and PPARγ in a corneal wound model [11][12][13]. On the other hand, our recent study showed that PPARβ/δ promotes neovascularization while suppressing inflammation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Fenofibrate treatment suppressed corneal neovascularization by reducing Vegf and Ang-2 mRNA expressions in a rat corneal alkali burn model [105]. The same group demonstrated that treatment with a mixture of fenofibrate/pioglitazone (combination of PPARα and PPARγ activation) also suppressed corneal neovascularization by reducing Vegf and Ang-2 mRNA expressions in a rat alkali burn model [106]. Another group showed that the oral administration of PPARα agonists (fenofibrate, WY14,643, ETYA, bezafibrate, and gemfibrozil) suppressed FGF2-induced corneal neovascularization [107].…”
Section: Eye Diseasesmentioning
confidence: 94%